1941
DOI: 10.1152/ajplegacy.1941.134.3.549
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Fixation in the Thyroid as Influenced by the Hypophysis and Other Factors

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1943
1943
1953
1953

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Goldsmith, Stanbury, and Brownell have recently demonstrated that the injection of preparations of this material causes an increase in the rate of release of hormone from the thyroid gland (6). Studies on the rat and chick have demonstrated similar changes (7)(8)(9)(10).…”
mentioning
confidence: 94%
“…Goldsmith, Stanbury, and Brownell have recently demonstrated that the injection of preparations of this material causes an increase in the rate of release of hormone from the thyroid gland (6). Studies on the rat and chick have demonstrated similar changes (7)(8)(9)(10).…”
mentioning
confidence: 94%
“…Radioiodine tracers have subsequently been utilized in many studies dealing with the thyroid of laboratory animals, in vitro experiments and clinical investigations. The method has been applied to the study of the biosynthesis of thyroid hormone (1, 3 to 9), the action of thyrotrophic hormones (4,10), the action of goitrogens (5,11) and of other factors influencing the function of the thyroid (6), the functional activity of various thyroid tumors and a number of other problems.…”
mentioning
confidence: 99%
“…The rate at which organic binding and coupling goes on depends on the state of activity of the gland, and is accelerated by thyrotropin (50) and exposure to cold (51), slowed by hypophysectomy (4,52), and influenced by the previous iodide level (36). The rate is also affected by the iodide concentration at any moment (32), as noted below.…”
Section: Organic Binding and Hormone Synthesismentioning
confidence: 98%
“…This assumption is perhaps unnecessary, however, since it has been found repeatedly that diiodotyrosine is rapidly destroyed in the body. Thus, Leblond and Sue (4) when the radioactivity first appears in the proteinbound iodine, it is predominantly in the diiodotyrosine-like fraction; later, it is chiefly in the thyroxine-like component (50).…”
Section: Hormone Secretionmentioning
confidence: 99%
See 1 more Smart Citation